Analisis Sistem Informasi Akuntansi Penjualan dalam Upaya Meningkatkan Efektivitas Pengendalian Intern (Studi Pada Perum BULOG Sub Divre Kediri) - Nurlailatul Fitriyah; Dwi Ari Pertiwi (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
This research aims to acknowladge how the application of accounting information system sales and the implementation of accounting information system sales in effort to improve internal control effektiveness at Perum Bulog Sub Divre Kediri. The research is a case study. The analyzed method were using the methods of analysis deskriptif. The result of this reasearch ishow that the application of accounting information system sales and the implementation of accounting information system sales in effort to improve internal control effektiveness at Perum Bulog Sub Divre Kediri most have been applicated and implemented in accordance with the theory formulate, then it can be concluded that the application of accounting information system sales and the implementation of accounting information system sales in effort to improve internal control effektiveness at Perum Bulog Sub Divre Kediri is running well.